Leakage from closed pressure relief valve caused by surface imperfections – analytical model and measurement - Romanik, Grzegorz; Rogula, Janusz; Romanik, Elżbieta (Instal, 2024)
The article presents a way to obtain a mathematical model enabling the calculation of leakage between the steel head and the steel seat of the Pressure Relief Valve. Local contact conditions described by the roughness parameters were taken into account. To verify the mathematical model, experimental tests of valve tightness were carried out using the helium detection method. The tests were carried out in the gas pressure range from 0 to 1 MPa. The contact pressure between the head and the seat ranged from 0 to 5 MPa. The analytical model showed convergence with the experiment for the recommended values of contact pressure for the head and seat made of metal. It seems that the constructed computational model can find engineering applications due to its simplicity.